Towards health with justice: Litigation and public inquiries as tools for tobacco control (Tobacco Free Initiative, World Health Organization, 2002)
This monograph has been developed by TFI in order to provide both countries and individuals at national, regional and global levels with information, support and technical assistance on litigation and public inquiries as tools for tobacco control. These two elements are key emerging techniques in the field of tobacco control. Therefore, it is crucial that public health workers seize this opportunity to step beyond the realm of science and medical statistics and embrace other techniques and tools for tobacco control. This monograph is based on the "Consultation on Litigation and Public Inquiries as Public Health Tools organized and held by WHO Regional Office for the Eastern Mediterranean Region, in collaboration with WHO headquarters, from 5 to 7 February 2001, in Amman, Jordan. During this Consultation, more than 20 Member States expressed an urgent need to understand the scope and magnitude of litigation and public inquires as tools for tobacco control in order to determine the best ways to combine science and law in curbing the tobacco epidemic.